Predictors associated with academic performance of medical students (Bangladesh Journal of Medical Science, 2026)
Aim Ensuring a high level of academic performance among students is an important task for higher education systems. This study aims to identify key predictors of academic success, measured by GPA, among medical students. Materials and Methods A cross-sectional study was conducted with the participation of 112 students of the Faculty of Medicine at Al-Farabi Kazakh National University. Data collection was carried out using a questionnaire distributed via Google Forms, which reflected demographic characteristics, indicators of school activity, and measures of quality of life and/or subjective well-being. Multiple logistic regression was used to assess the influence of factors. Results The analysis showed that school performance significantly affects GPA: an increase in the level of school grades increased the likelihood of achieving a high GPA (Exp(B)=2.188, p=0.047). Sleep quality was another significant predictor: a decrease in sleep quality reduced GPA (Exp(B)=0.276, p=0.002). Maintaining a stable standard of living was associated with a higher GPA (Exp(B)=2.030, p=0.033). Factors such as gender, material well-being, and family relationships demonstrated borderline significance, requiring further analysis. Conclusion The results highlight the importance of academic preparation, quality of life, and emotional stability for achieving high academic performance. These findings may serve as a basis for the development of targeted interventions aimed at improving student success, as well as for identifying priority areas in medical education research.BJMS, Vol. 25 No. 01 January’26 Page : 312-316